Vocational High School Students' Competency Needs to the World of Work - Sri Rahmadhani; Ahyanuardi; Lili Suryati (Universitas Pendidikan Ganesha, 2022)
The high unemployment rate is certainly different from the goal of SMK, which should be a ready-to-work workforce. It is influenced by the lack of employment opportunities and the weak competence of graduates in the field of expertise. In addition, qualified educators are needed so that they can improve students' competencies and skills. This study aims to analyze the competency needs of vocational students for the world of work. This alternative can be seen from the curriculum used by Vocational High Schools and the competencies produced by the needs of the world of work oriented to the standards of the Indonesian National Qualifications Framework. This type of research is qualitative. The method used in this research is the Mixed Method, by combining quantitative research and qualitative research. The instrument used in collecting data is a questionnaire. The data analysis technique used the respondent achievement level (TPR) with the Milles and Huberman model. The results of this study indicate a weakness in the competence of SMK graduates to the competence needs of the world of work, with a percentage gain of 45.61%. These weaknesses appear in the skills possessed by students to the needs of the world of work. It means that there is a need for improved analysis to be in the good and excellent categories in the future. The competence of SMK graduates can refer to the competency needs that exist in the world of work and reduce unemployment at the SMK level.